2015
DOI: 10.1159/000430381
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Liver Regeneration

Abstract: Liver maintains a unique tremendous regeneration capacity in response to partial hepatectomy (PH) or injury. Hepatocyte proliferation critically contributes to the process of liver regeneration (LR), which is regulated by various cytokines and growth factors. However, the molecular basis of LR remains unclear. Emerging evidence indicates that microRNAs (miRNAs, miRs) are involved in controlling hepatocyte proliferation during LR. In this review, an overview is provided to cover recent achievements in studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 105 publications
0
30
0
Order By: Relevance
“…To investigate the circRNA regulatory role in rat LR further, GO analysis was performed to annotate the biological functions of host linear transcripts during priming phase of rat LR, the result showed obviously that a significant amount of GO terms were related with the response to stress, energy metabolism and regulation of cell proliferation, which had been acknowledged as the important activities in the early stage of rat LR [1, 22, 31, 32]. The most enriched CC terms were about different kinds of plasma membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the circRNA regulatory role in rat LR further, GO analysis was performed to annotate the biological functions of host linear transcripts during priming phase of rat LR, the result showed obviously that a significant amount of GO terms were related with the response to stress, energy metabolism and regulation of cell proliferation, which had been acknowledged as the important activities in the early stage of rat LR [1, 22, 31, 32]. The most enriched CC terms were about different kinds of plasma membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation was the most important physiological activity during rat LR [22]. Consequently, an intriguing possibility was raised that alternative circRNA formation might constitute a novel regulatory layer in rat LR.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), non-coding short RNA molecules composed of 20-25 nucleotides, negatively regulate gene expression at the post-transcriptional level by binding to the 3’-UTR region of target mRNAs, thereby inhibiting translation or inducing mRNA degradation [5]. Prior studies have noted that miRNAs play a critical role in vascular diseases through regulating VSMCs and endothelial cell functions, such as proliferation, migration, apoptosis, and synthesis/secretion of ECM proteins [8-10].…”
Section: Introductionmentioning
confidence: 99%
“…Some reports estimate that about 50% of human protein-coding genes are subject of miRNA regulation (Huntzinger and Izaurralde, 2011). Consistently, several studies have reported the involvement of miRNAs in hepatic differentiation of stem cells, liver development, and liver regeneration (Davoodian et al, 2014a;Chen et al, 2015;Mahgoub and Steer, 2016). Consistently, several studies have reported the involvement of miRNAs in hepatic differentiation of stem cells, liver development, and liver regeneration (Davoodian et al, 2014a;Chen et al, 2015;Mahgoub and Steer, 2016).…”
Section: Introductionmentioning
confidence: 71%
“…Notably, several miRNAs have been recently reported to be involved in hepatic differentiation of stem cells suggesting their critical role in differentiation induction (Cui et al, 2013;Davoodian et al, 2014b;Jung et al, 2016). Several studies have highlighted the importance of miR-122 involvement in liver proliferation, regeneration, and development Kim et al, 2011;Doddapaneni et al, 2013;Davoodian et al, 2014a;Chen et al, 2015;Raut and Khanna, 2016). Several studies have highlighted the importance of miR-122 involvement in liver proliferation, regeneration, and development Kim et al, 2011;Doddapaneni et al, 2013;Davoodian et al, 2014a;Chen et al, 2015;Raut and Khanna, 2016).…”
Section: Discussionmentioning
confidence: 99%